2015
DOI: 10.15740/has/ijpp/8.1/61-64
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of major sucking pests infesting niger and their relation to weather parameters

Abstract: Investigations were carried out on population dynamics of major insect pests on niger (Guizotia abyssinica L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…The present findings are in agreement with Singh et al [19] who reported significant positive influence of temperature on population of the leafhopper. Leafhopper population was positively correlated with temperature, relative humidity and wind speed while negative correlation with rainfall, which corroborates the finding of Parsad et al [20] who reported positive correlation between jassid population and relative humidity.…”
Section: Discussionsupporting
confidence: 90%
“…The present findings are in agreement with Singh et al [19] who reported significant positive influence of temperature on population of the leafhopper. Leafhopper population was positively correlated with temperature, relative humidity and wind speed while negative correlation with rainfall, which corroborates the finding of Parsad et al [20] who reported positive correlation between jassid population and relative humidity.…”
Section: Discussionsupporting
confidence: 90%
“…The field was left as such without any plant protection intervention. Whitefly population were recorded from three leaves per plant top, middle and bottom canopies (randomly sampled tagged 10 plants per plot) from each plot were enumerated at weekly interval [6]. The meteorological data during the study periods was also recorded from the AICRP on Agro-meteorology, Directorate of Research, BCKV, Kalyani, Nadia to establish the correlation and regression co-efficient between whitefly population and weather factors.…”
Section: Methodsmentioning
confidence: 99%
“…Biswal and Patel [11] identified aphid, whitefly and thrip's were the first to infiltrate and colonize the field crop, followed by leaf miner, and remained active until the crop was harvested.…”
Section: Incidence Of Aphidmentioning
confidence: 99%